Use of Novel Concussion Protocol With Infralow Frequency Neuromodulation Demonstrates Significant Treatment Response in Patients With Persistent Postconcussion Symptoms, a Retrospective Study - Legarda, Stella B.; Lahti, Caroline E.; McDermott, Dana; Michas-Martin, Andreas (Frontiers in Human Neuroscience, 2022)
Introduction - Concussion is a growing public health concern. No uniformly established therapy exists; neurofeedback studies report treatment value. We use infralow frequency neuromodulation (ILF) to remediate disabling neurological symptoms caused by traumatic brain injury (TBI) and noted improved outcomes with a novel concussion protocol. Postconcussion symptoms (PCS) and persistent postconcussion symptoms (PPCS; >3 months post head injury) are designated timelines for protracted neurological complaints following TBI. We performed a retrospective study to explore effectiveness of ILF in PCS/PPCS and investigated the value of using this concussion protocol. Method - Patients with PCS/PPCS seen for their first neurology office visit or received their first neurofeedback session between August 1, 2018 and January 31, 2021 were entered. Outcomes were compared following treatment as usual (TAU) versus TAU with ILF neurotherapy (TAU+ILF). The study cohort was limited to PPCS patients; the TAU+ILF group was restricted further to PPCS patients receiving at least 10 neurotherapy sessions. Within the TAU+ILF group, comparisons were made between those who trained at least 10 sessions using concussion protocol (TAU+ILF+CP) and those who trained for at least 10 sessions of ILF regardless of protocol (TAU+ILF-CP). Results - Among our resultant PPCS cohort (n=59) leading persistent neurological complaints were headache (67.8%), memory impairment (57.6%), and brain fog (50.8%). PPCS patients in TAU+ILF+CP (n=25) demonstrated greater net (p=0.004) and percent (p=0.026) improvement of symptoms compared to PPCS subjects in TAU (n=26). PPCS patients in TAU+ILF-CP (n=8) trended towards significant symptom improvements compared to TAU, and TAU+ILF+CP trended towards greater efficacy than TAU+ILF-CP. Conclusions - PPCS patients who received TAU+ILF+CP demonstrated significantly greater improvement as a group when compared to TAU. When used as an integrative modality to treatment as usual in managing patients with PPCS, ILF neuromodulation with use of concussion protocol provided significant symptom improvements.